Enoque: nos bastidores de crenças angelologicas do cristianismo primitivo - Guimarães, Filipe de Oliveira (2011)
The research constitutes a quest to rescue the understanding of epistemology angelology present in early Christianity. Since the Bible makes mention of the book of Enoch, we sought to harmonize the accounts so that some biblical texts could be seen more clearly. In the book of Jude, for example, there is a prophecy attributed to Enoch, however, this prophecy is not found in the Bible, which begs the question: Where Judas taken this prophecy? The prophecy is present in the Book of Enoch, more precisely in the Book of Watchers. Reading the Book of Watchers introduces the reader in an interesting world that discusses about the fall of angels, giants, flood, demons and visions. Such reports, present in Enoch, complete biblical narratives giving them a very interesting harmony. In an attempt to know the influence of Enoch in Judaism, allowed us to find quotes from the book present in Jewish writings, and quotes made by the leaders of early Christianity. In both cases there was extensive use of the Book of Watchers corroborating the finding that the book was a significant influence on the thought of Judaism and Christianity angelology primitive. Keywords: Enoch, early Christianity, Angelology.